Produção de etanol a partir do coco verde utilizando cepas de Saccharomyces cerevisiae industriais - Soares, Jimmy (2016)
Cocos nucifera L., coconut, is a palm of high commercial importance with various applications in the food industry. The coconut products in Brazil are the shredded coconut, coconut milk, coconut water, and coconut oil. Additionally, the aseptic packaging of coconut water is considered a high potential product due the improved distribution and extended expiration date. Coconut water is obtained from the green coconut fruits, but the remaining biomass does not have a useful destination and is a waste problem in the in cities of the main producer countries. The green coconut is composed by cellulose, hemicelulose and lignin, and the cellulose and hemicellulose can be converted in fermentable sugars to produce bioethanol. Bioethanol is a renewable biofuel with potential to address the problems caused by the fossil fuels consumption. This study comprises the ethanol production from coconut hydrolysates submitted to an alkaline pretreatment, and fermented by different Saccharomyces cerevisiae strains. High-solid loadings of biomass in a simple batch or fed-batch processes were used to produce hydrolysates with high sugar level. The main coconut structure is the mesocarp, and this structure was investigated in different pretreatment conditions for the hydrolysate production, like the alkali concentration, pretreatment duration and enzyme load. High-solid load in a single batch produced 7- 8% (w/v) sugars, which resulted in 3.7% (v/v) ethanol when fermented by a 2G yeast strain. The commercial enzyme load was also reduced with minor modifications in the sugar and ethanol yield. On the other hand, the production of hydrolysates using the whole green coconut fruit using single batch resulted in only 6.2% (w/v) sugars. The fed-bath aimed to contour some limitation of the single batch and produce hydrolysates with more sugars. The fed-batch resulted in hydrolysates from the mesocarp and coconut with more sugars, 9.7% (w/v) and 7.2% (w/v), respectively. Mesocarp hydrolysate from the fed-batch process was easily fermented and resulted in 4.3% (v/v) ethanol. Coconut hydrolysate showed a slow fermentation due the presence of fermentation inhibitors, and the ethanol titer was 3.8% (v/v). The removal of inhibitors resulted in a fast fermentation of the coconut hydrolysate, however the inhibitors removal step resulted in sugar loss, and a lower ethanol titer of 2.5% (v/v). The processes established in this study to produce ethanol from coconut are simple when compared to other processes proposed to this biomass, and also resulted in higher ethanol titer. The production in the range of 4% (v/v) ethanol from coconut showed the potential of this biomass, which should benefit the coconut producer countries.